PERSEPSI DAN PARTISIPASI KTH TERHADAP AGROFORESTRY DI KAWASAN PENYANGGA TAHURA SUTAN SYARIF HASYIM - Eni - Suhesti; Hadinoto - Hadinoto (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2019)
This study aims to measure perceptions and participation of forest farmer group/Kelompok Tani Hutan (KTH)and analyze the influence of their perceptions and participation in agroforestry activities so as to rehabilitate critical land in the buffer zone of Sultan Syarif Hasyim Forest Park (Tahura SSH) Riau Province. Measurement of perceptions and participation of respondents is carried out by using an instrument in the form of a questionnaire that refers to Likert scale. The research instrument is tested for its validity and reliability. Data analysis is carried out descriptively to describe the level of perception and participation, while simple non parametric linear regression analysis is applied to determine the effect of the perceptions on participation. Results of the study reveal that KTH members involved in agroforestry activities for critical land rehabilitation in Sultan Syarif Hasyim Tahura buffer zone have a perception in the category of good 77.78%, moderate as much as 7.49% and bad as much as 14.29% for these activities. While the level of participation in the category of high is 41.27%, moderate category is 39.68%, and low is 19.05%. Their perceptions effect significantly to the participation of KTH members in agroforestry.